Developing Book Creator Application as Students’ Worksheet in Reading Narrative Text - Lestari, Ayu; Harahap, Neni Afrida Sari (CV. PUSDIKRA MITRA JAYA, 2025)
This study aimed to develop a Book Creator application-based worksheet for teaching reading narrative texts to junior high school students. The research employed the Research and Development (R&D) method, adapting Borg and Gall’s (2007) model into six stages: research and information collection, data analysis, product design, expert validation, revision, and final product development. Data were collected through student needs analysis questionnaires, and expert validation questionnaires. Based on these findings, the research was carried out through six steps. First, Gathering data and information from students using questionnaires to understand their needs, lacks, and learning needs. Second, Data analysis were analyzed as the foundation for material development. Third, a draft worksheet was developed using Book Creator Application focusing on interactive and structured activities. Fourth, the draft was evaluated through expert validation to ensure its content, design, and relevance. Fifth, revisions were made based on expert feedback to improve clarity and effectiveness. Finally, the validated product received as score of 4.1 in the “good” category, indicating that the developed worksheet is suitable for use in teaching reading narrative texts.